Development of a new sustainable packaging paper based on cellulose filaments and refined kraft pulp - Lahbib Abenghal; Julien Bley; Balazs Tolnai; Guy Njamen; Bruno Chabot (Future Foods)
The traditional use of single-use plastics in the packaging sector is limited by pollution, non-recyclability, and non-biodegradability. Replacing it with recyclable, biodegradable, and compostable materials such as cellulose has become vital. In this study, mixtures of refined kraft pulp and cellulose filaments were used to produce paper with good barrier properties. The results showed that cellulose filaments significantly improved the barrier properties of the handsheets without the use of other chemical agents. The water vapor transmission rate (WVTR) of samples produced from refined kraft pulp alone was 177 g/m2. day, which significantly decreased to 77 g/m2. day by the addition of 80 % cellulose filaments owing to the formation of a complex network of physical and chemical bonds between the fibers. The water barrier also improved significantly as the Cobb60 value decreased from 87 to 57 g/m2 when 80 % cellulose filaments were used. Furthermore, all the samples produced had a recyclability percentage of more than 89 %, which is an essential requirement in the packaging industry.